Evaluation of Volatile Profile and In Vitro Antioxidant Activity of Fermented Green Tea Infusion With Pleurotus sajor-caju (Oyster Mushroom) - Su, Wei-Ying; Gao, Shu-Yi; Zhan, Si-Jia; Wu, Qi; Chen, Gui-Mei; Han, Jin-Zhi; Lv, Xu-Cong; Rao, Ping-Fan; Ni, Li (Frontiers in Nutrition, 2022)
Green tea has distinct astringency, bitter taste, and typical green flavor because of its post-harvest treatment without withering and enzymatic oxidation. Microbial fermentation has been identified as a promising strategy that could give green tea infusion a special taste flavor. This might be linked to the metabolic transformation ability of microorganisms. In this study, starter culture of edible mushroom Pleurotus sajor-caju (oyster mushroom) was used for submerged fermentation of green tea infusion in order to improve its flavor and taste quality. The volatile profile determined by headspace solid-phase microextraction, coupled with gas chromatography mass spectrometry, showed that the contents of (Z)-2-penten-1-ol and methyl heptadienone in green tea infusion were decreased significantly by the fermentation with the basidiomycete P. sajor-caju (p < 0.01), which would alleviate the herbal and grass flavor of green tea infusion to a certain extent. Meanwhile, the contents of linalool and geraniol were increased 9.3 and 11.3 times, respectively, whereas methyl salicylate was newly produced after fermentation by P. sajor-caju, endowing the fermented tea infusion with a pleasant flower and fruit aroma. In addition, the polyphenol profile was determined using high-performance liquid chromatography equipped with ion trap mass spectrometry, and the results indicated that the contents of most polyphenols in green tea infusion decreased significantly after fermentation by P. sajor-caju. The reduction of catechins and anthocyanins in fermented green tea infusion alleviated the astringency and bitterness. Moreover, the antioxidant activity of fermented green tea infusion was obviously decreased, especially the DPPH-free radical-scavenging ability and the ferric-reducing power. However, it is noteworthy that the ABTS-free radical scavenging ability was improved compared with the unfermented one, indicating that the increased tea pigments and volatile metabolites (such as linalool and geraniol) after fermentation with P. sajor-caju may also contribute to the antioxidant capacity of fermented green tea infusion. Overall, the innovative approach driven by P. sajor-caju fermentation has achieved promising potential to manipulate the green tea flavor.